Enantioselective Stereodivergent Synthesis of Jaspine B and 4-epi-Jaspine B from Axially Chiral Allenols - Alnazer, Heba; Castellan, Tessa; Salma, Yahya; Génisson, Yves; Ballereau, Stéphanie (Synlett, 2019)
A short enantioselective synthetic route to the cytotoxic marine natural product jaspine B has been developed. A chiral non-racemic primary α-allenol, obtained from pentadecanal, gave access to an enantioenriched 2-tetradecyl-2,5-dihydrofuran as key intermediate. A stereodivergent functionalization of this dihydrofuran allowed access in a few steps to jaspine B and its 4-epimer.
Keywords: jaspine B; pachastrissamine; allenol; enatioselective allenylation; epoxydation